Sonication-assisted liquid phase exfoliation of two-dimensional CrTe3 under inert conditions - Synnatschke, Kevin; Moses Badlyan, Narine; Wrzesińska, Angelika; Lozano Onrubia, Guillermo; Hansen, Anna-Lena; Wolff, Stefan; Tornatzky, Hans; Bensch, Wolfgang; Vaynzof, Yana; Maultzsch, Janina; Backes, Claudia (Ultrasonics sonochemistry, 2023)
Liquid phase exfoliation (LPE) has been used for the successful fabrication of nanosheets from a large number of van der Waals materials. While this allows to study fundamental changes of material properties’ associated with reduced dimensions, it also changes the chemistry of many materials due to a significant increase of the effective surface area, often accompanied with enhanced reactivity and accelerated oxidation. To prevent material decomposition, LPE and processing in inert atmosphere have been developed, which enables the preparation of pristine nanomaterials, and to systematically study compositional changes over time for different storage conditions. Here, we demonstrate the inert exfoliation of the oxidation-sensitive van der Waals crystal, CrTe3. The pristine nanomaterial was purified and size-selected by centrifugation, nanosheet dimensions in the fractions quantified by atomic force microscopy and studied by Raman, X-ray photoelectron spectroscopy (XPS), energy-dispersive X-ray spectroscopy (EDX) and photo spectroscopic measurements. We find a dependence of the relative intensities of the CrTe3 Raman modes on the propagation direction of the incident light, which prevents a correlation of the Raman spectral profile to the nanosheet dimensions. XPS and EDX reveal that the contribution of surface oxides to the spectra is reduced after exfoliation compared to the bulk material. Further, the decomposition mechanism of the nanosheets was studied by time-dependent extinction measurements after water titration experiments to initially dry solvents, which suggest that water plays a significant role in the material decomposition.
Online veröffentlicht: 19. Juli 2023
Gesehen am 11.06.2024